Talking about tasks or just sharing job offers? : A case study on job-related tweets - Hein, Kristine [Verfasser]; Tiemann, Michael [Verfasser]; Dörpinghaus, Jens [Verfasser] (My University, 2025)
"The skills and qualifications of IT professionals are constantly changing and under discussion. In particular, we see the impact of emerging technologies and tools, such as AI, on the labor market and their reflection in the broader scientific community, media and everyday life. Several approaches have discussed how to assess the impact of computer science education from the perspective of education and labor market research. However, in order to uncover the complex dynamics surrounding vocational education, we need to take a closer look at the labor demand as well as the public perception and valuation of professionals. Therefore, we present a novel approach to work with social media data, in particular Twitter/X data. We have collected a large dataset of job-related X data (2007-2023) but see that a word list-based searching strategy is not enough. Most tweets are actually job offers and we will discuss several strategies to categorize tweets accordingly to make a meaning out if it. We focus on occupations in natural sciences, geography and informatics." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; L 4.1.2 Elektronische Medien; G 2.3.4 Qualifikationswandel; 370; Arbeitsmarktforschung; Soziales Netzwerk; Social Media; Qualifikationswandel; Datenanalyse; Regressionsanalyse; Linguistik